The Hypothalamic-Pituitary-Adrenal Axis in Health and Disease : Cushing's Syndrome and Beyond - Geer, Eliza B. (Springer International Publishing : Imprint: Springer, 2017)
Cushing´s syndrome is a rare disorder that is associated with many co-morbidities such as systemic hypertension, diabetes, osteoporosis, impaired immune function, and psychiatric disease, all of which severely reduce quality of life and life expectancy. This book reviews the role of cortisol in the human body, focusing on the effects of excess cortisol due to Cushing's syndrome as well as the role of the HPA axis in metabolism, inflammation, and neuropsychiatric function. The volume will cover basic mechanistic data, clinical outcomes data, and novel therapies. Also discussed are everything from abnormalities of the HPA axis, to the role of the HPA axis in the development of neuropsychiatric disorders and metabolic disorders, to new definitions of Cushing's remission and recurrence. The Hypothalamic Pituitary Adrenal Axis in Health and Disease will provide a comprehensive and multi-disciplinary review of the pathophysiology and outcomes of excess cortisol in the human body and brain as well as the role of the HPA axis in other disease states.
Keywords: Medicine.; Endocrinology.; Systems biology.; elektronické knihy; electronic books